THE NATIONAL BAPTIST CONVENTION: AN EXPRESSION OF THE BLACK FREEDOM - Patricia Rintho Wahyu Angraini (Soegijapranata Catholic University, 2004)
the history of black America is miserable. Their ancestors coming from West Africa were taken to America trough the South to become slaves. Their human rights wee banned for centuries. They lived in a democratic country, America, but they had no right to live properly. They dreamt to have a life as the whites had. In the nineteenth century, it happened that a rat development in Protestant Christendom opened the opportunity for the establishment of black churches. The National Baptist Convention, whose major followers were blacks, was a denomination that existed in America. This denomination accommodated the aspiration of freedom for the blacks in America.